Pregnant women infected with pandemic influenza A(H1N1)pdm09 virus showed differential immune response correlated with disease severity - Periolo, Natalia (2015)
Background: During pregnancy, immunological and hormonal alterations place women at increased risk for influenza-related severe illnesses including hospitalization and death. Although A(H1N1) pdm09 infection resulted in increased disease severity in pregnant women, the precise mechanisms responsible for this risk have yet to be established. Objectives: The present study was aimed to investigate the role of host chemokines and cytokine profiles in A(H1N1) pdm09 infection regarding disease severity in pregnant women. Study design: This retrospective survey examined 41 pregnant women with confirmed A(H1N1) pdm09 infection. Of them, 12 died (D), 29 survived (S), and 17 remained uninfected and served as controls (C). Antiviral response was evaluated for IFN-β expression and gene expression profiles of cytokines (TNF-α, IL-6, IL-12, TGF-β) and chemokines (IL-8, RANTES, MCP-1, IP-10), and the viral Matrix (M1) gene was quantified and normalized using the housekeeping gene product β-actin mRNA. Results: Higher IL-8 and TNF-α mRNA expression were found in D and S compared with C, while IL-6 showed higher expression in D. Interestingly, these results were associated with a decrease in the anti-inflammatory response of TGF-β mRNA and IFN-β. These alterations would lead to an imbalance in the immune response of those patients. Conclusions: Pregnancy-related reductions in IFN-β and TGF-β expression levels and elevated levels of pro-inflammatory cytokines could explain the increased severity of infection and death of pregnant women. These findings may help improve the understanding of the high susceptibility and disease severity to influenza virus infection during pregnancy.